A Criticism of the Argument for the Possibility of Religious Science - Taqavi, Mostafa (Theology and science, 2025)
Having quoted a number of cases from contemporary science, some philosophers have shown that science has naturalistic biases and argued that in his encounter with such a science one can defend the possibility of religious (or Augustinian) science. In this essay we have shown that “argument of the possibility of religious science” can only prove the possibility of “science influenced by religion” not the “possibility of religious science”. To this end, we have studied three issues: I) religious science, II) presuppositions that play a role in the formation of scientific content, and III) those norms that orient empirical data collection.